Islamic Education in the Digital Era: Between Learning Innovation and Moral Challenges - M. Habib; Rosdialena (Konsultan Jurnal Ilmiah Indonesia, 2026)
The development of digital technology has brought about fundamental changes in the world of education, including Islamic education, which now faces both opportunities for innovation and moral challenges that cannot be ignored. This study aims to comprehensively examine the dynamics of Islamic education in the digital age, covering forms of technology-based learning innovations and the moral challenges posed by digital exposure to students. The method used is library research with a qualitative-descriptive approach through content analysis of various relevant and up-to-date scientific literature sources. The results indicate that innovations in Islamic education during the digital era include the use of e-learning platforms, blended learning, and interactive media based on information technology, which have been proven to enhance the effectiveness and engagement of students. However, on the other hand, the digital era also poses serious threats, such as moral degradation, exposure to negative content, and the weakening of Islamic character among the younger generation. This study concludes that the integration of Islamic values into every aspect of digital learning is a strategic solution that must be implemented systematically through the strengthening of the curriculum, teacher competencies, and the role of the family. The contribution of this study lies in offering an integrative conceptual framework between technological innovation and the strengthening of moral character in contemporary Islamic education.